Magmatic Activity and Dynamics of Melt Supply of Volcanic Centers of Ultraslow Spreading Ridges: Hints From Local Earthquake Tomography at the Knipovich Ridge. (7th October 2022) - Meier, M.; Schlindwein, V.; Schmid, F.
Abstract: Along ultraslow spreading ridges melt is distributed unequally, but melt focusing guides melt away from amagmatic segments toward volcanic centers. An interplay of tectonism and magmatism is thought to control melt ascent, but the detailed process of melt extraction is not yet understood. We present a detailed image of the seismic velocity structure of the Logachev volcanic center and adjacent region along the Knipovich Ridge. With travel times of P‐ and S‐waves of 3, 959 earthquakes we performed a local earthquake tomography. We simultaneously inverted for source locations, velocity structure and the Vp/Vs‐ratio. An extensive low velocity anomaly coincident with high Vp/Vs‐ratios >1.9 lies underneath the volcanic center at depths of 10 km below sea level in an aseismic area. More shallow, tightly clustered earthquake swarms connect the anomaly to a shallow anomaly with high Vp/Vs‐ratio beneath the basaltic seafloor. We consider the deep low‐velocity anomaly to represent an area of partial melt from which melts ascent vertically to the surface and northwards into the adjacent segment. By comparing tomographic studies of the Logachev and Southwest Indian Ridge Segment‐8 volcano we conclude that volcanic centers of ultraslow spreading ridges host spatially confined, circular partial melt areas below 10 km depth, in contrast to the shallow extended melt lenses along fast spreading ridges. Lateral feeding over distances of 35 km is possible at orthogonal spreading segments, but limited at the obliquely spreading Knipovich Ridge. Plain Language Summary: Mid‐ocean ridges mark the tectonic plate boundaries, where the plates drift apart. Fresh magma rises into the gap and builds new seafloor. The slower the plates drift apart, the less magma is present underneath the ridge. At very slow spreading ridges there is not enough magma to build new seafloor along the entire length of the ridge. Rather, melt is guided toward individual volcanic centers spaced at about 100 km, where melt accumulates and ascents. In our study we try to find melt storage areas and ascent paths of such a volcanic center. With velocities of different seismic wave types from earthquakes we map the velocity structure of the area underneath the major Logachev volcanic center. Lower velocities indicate an area partly including melt at depths of more than 10 km, far deeper than at mid‐ocean ridges with sufficient melt supply. From the deep magma reservoir, many earthquake swarms map the long ascent path of melt to the surface. The interplay of magmatic and tectonic activity is important here. In a comparison with results from another volcanic center, we find that lateral magma feeding is possible in orthogonal spreading, but limited in oblique spreading, as at the Knipovich Ridge. Key Points: Active volcanic centers at ultraslow spreading ridges host deeper and more confined partial melt areas than faster spreading ridges Earthquake swarms delineate melt ascent paths from the partial melt area to the surface Lateral feeding at shallow depths into subordinate segments is prevented by ridge obliquity